2016
DOI: 10.1136/bcr-2015-213058
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic pregnancy in an undescended fallopian tube: a diagnostic challenge

Abstract: Uterine malformations are the most frequent anomalies of the Müllerian ducts, but undescended ovaries and fallopian tubes are very rare congenital defects. Pregnancy in these misplaced organs may occur, frequently posing a diagnostic challenge. A case of a ruptured ectopic pregnancy in an undescended fallopian tube associated with other genital malformations is presented. This case provides evidence for the recognised phenomenon of peritoneal gametes or embryo transmigration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Several cases reveal the phenomenon of transperitoneal gamete/embryo migration. [ 13 ] The absence of a tubal connection with the unicornuate uterus and the presence of a corpus luteum in the contralateral ovary may serve as evidence for it. It remains unknown whether chemotactic or other factors are involved in the transport of gametes or embryos across the peritoneal cavity to reach the contralateral and heterotopic tube.…”
Section: Discussionmentioning
confidence: 99%
“…Several cases reveal the phenomenon of transperitoneal gamete/embryo migration. [ 13 ] The absence of a tubal connection with the unicornuate uterus and the presence of a corpus luteum in the contralateral ovary may serve as evidence for it. It remains unknown whether chemotactic or other factors are involved in the transport of gametes or embryos across the peritoneal cavity to reach the contralateral and heterotopic tube.…”
Section: Discussionmentioning
confidence: 99%
“…While uterine anomalies are the most frequent of the Müllerian ducts abnormalities, occurring in 2% to 4% of fertile women, structural abnormalities of the fallopian tubes and ovaries are exceedingly rare 6. While studies have reported rudimentary horn pregnancies, as well as tubal and cornual ectopic pregnancies occurring in both communicating and non-communicating horns,7 there is little published literature about ectopic pregnancies in the undescended ovary or tube in patients with an isolated unicornuate uterus.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy in an undescended tube is a scarce type of ectopic pregnancy [1]. Only a few cases have been reported so far, posing a diagnostic challenge [2,3]. Our case constitutes transperitoneal gamete transportation evidence from the contralateral tube to the hypoplastic tube located outside of the pelvis [4].…”
mentioning
confidence: 84%